Hungry wintering birds and angry farmers: Crop damage and management implications in a protected wetland in China - Lanyan Zhong; Yanfang Li; Yalong Li; Chuanyin Dai (Global Ecology and Conservation)
Wetland degradation can be caused by inappropriate protection and restoration measures and lead to a gradual loss of foraging sites for waterbirds. Consequently, birds are beginning to depend on farmland around protected wetlands, resulting in conflict between agricultural and conservation aims. Avian crop damage often provokes negative attitudes in farmers, which make them reluctant to support conservation. We investigated the characteristics of and local farmers’ responses to avian crop damage in a protected peri-urban wetland in China, where protection has changed its plant community and many wintering waterbirds forage on cropland. Ten species were found to be responsible for crop damage, with the most problematic being the Black-necked Crane (Grus nigricollis), which mainly damages potato, maize and napa cabbage. The farmers had negative attitudes toward the problematic species and a low tolerance for crop-foraging activity. Both traits were affected by measurable factors related to crop loss. The majority of the farmers interviewed (81.6 %) reported adopting measures to cope with birds’ crop exploitation, but with little effect. We recommend that the local government creates foraging sites within protected wetland in which food quality or density is superior to that of surrounding farmland, for example by modifying the invasive reed community to a suitable foraging site, inviting local farmers to grow crops but leave some unharvested in the planned area, or provisioning birds directly during periods of peak bird damage. Otherwise, financial compensation and insurance against crop losses should be considered. This study highlights the importance of understanding the critical link between wintering birds and farmers in wetland conservation practice.